Literature as a gift: 20 years since José Saramago’s Nobel Prize in literature (Philology, 2026)
Reis, Carlos (Org.) José Saramago. Nascido para Isto. Conferências do Congresso Internacional “José Saramago: 20 anos com o Prémio Nobel”. Lisboa, Ed. Fundação José Saramago, 2020, 253 p. ISBN 978-989-95820-7-1.